Caspase-11 contributes to site-1 protease cleavage and SREBP1 activation in the inflammatory response of macrophages - Cheng, Yinglan; Manabe, Ichiro; Hayakawa, Sumio; Endo, Yusuke; Oishi, Yumiko (Frontiers in Immunology, 2023)
Sterol regulatory element-binding proteins (SREBPs) are key transcription factors that control fatty acid and cholesterol metabolism. As the major SREBP isoform in macrophages, SREBP1a is also required for inflammatory and phagocytotic functions. However, it is insufficiently understood how SREBP1a is activated by the innate immune response in macrophages. Here, we show that caspase-4 (formerly caspase-11) is a novel inflammatory activator of SREBP1 in macrophages. Upon LPS treatment，caspase-4 was found to promote the processing of site-1 protease (S1P), an enzyme that mediates the cleavage and activation of SREBP1. We also determined that caspase-4 directly associates with S1P and cleaves it at a specific site. Furthermore, Casp4 deletion impaired the activation of S1P and SREBP1 as well as altered the expression of genes regulated by SREBP1 in macrophages. These results demonstrate that the caspase-4/S1P/SREBP1 pathway activates SREBP1 in response to LPS, thus regulating subsequent macrophage activation.